Form for reporting Iowa Christmas bird counts to Iowa Bird Life, Larry Farmer, March 1988 - Farmer, Larryet al (1988)
Iowa Christmas bird counts of regular and uncommon species found in Westfield contributed by Larry Farmer, March 1988. This item was submitted past the deadline for the Iowa Ornithologists Union Quarterly Report of winter 1987-1988. Epson - sheet feed